Federation Account Allocated Funds and Economic Growth in Nigeria: A Pre and Post Democracy Dispensation Assessments - Omodero, Cordelia Onyinyechi; Ihendinihu, John Uzoma; Dandago, Kabiru Isa (International Journal of Economics and Financial Issues, 2019)
The study investigates the impacts of federation account allocated funds on economic growth in Nigeria prior to reinstatement of democracy and after the restoration witnessed in May 29, 1999. The study employs annual time series data from 1989-1998 for pre restoration evaluation while data employed for post reinstatement assessment span from 2007-2016. All data were collected from CBN Statistical Bulletin, 2016 edition. Ordinary Least Square (OLS) method was used to perform the multi-regression analysis with the aid of Statistical Package for Social Sciences (SPSS) version 20. The findings of the study disclose that FAFG has a significant positive impact on RGDP after restoration of democracy while prior to restoration of democracy, the result reveals an insignificant negative influence on RGDP. FASG has insignificant positive impact on RGDP both on pre and post restoration of democracy while FALG has insignificant negative impact on RGDP in both scenarios tested. This leads to a conclusion that mismanagement of funds by the three tiers of government in Nigeria is responsible for dwindling economic growth in Nigeria and recommends proper use of resources by all levels of government in the country. Keywords: Federation account, revenue allocation, democracy, economic growth, government JEL Classifications: H71, H77, H79 DOI: https://doi.org/10.32479/ijefi.7794